2009
DOI: 10.3724/sp.j.1011.2009.00517
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation and spatial distribution of the root systemof corn in a soil profile

Abstract: The development of the root system of corn in soil profile is an indispensable parameter for the estimation of corn growth.The distribution of the root system can be used to evaluate the influence of climate on vegetative growth. This constitutes a creative scientific management and development system of water-saving agriculture. In the Gucheng Agro-meteorological Field Experimental Station of Chinese Academy of Meteorological Sciences, root length, root areal reach, root depth and root dry-weight of "Tunyu 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Other than C m , results show that among all the meteorological and agricultural explanatory variables considered (see Methods), precipitation ( P ), fertilizer use rate ( F ) and crop type ( c ) are most significant in influencing the soil moisture at the three soil depths considered. Here we take the 20–50 cm soil layer, which comprises a large portion of root zone 28 29 and is directly affected by transpiration, to illustrate the correlated effects of declining soil moisture. The analysis yields slopes of 4.1 × 10 −4 (m 3 m −3 mm −1 yr), −3.0 × 10 −4 (m 3 m −3 kg −1 ha yr), −0.013 and −0.026, for P , F , crop group 2 (i.e., c 2, wheat) and group 3 (i.e., c 3, maize and rapeseed), respectively – see model (1) in Methods.…”
Section: Resultsmentioning
confidence: 99%
“…Other than C m , results show that among all the meteorological and agricultural explanatory variables considered (see Methods), precipitation ( P ), fertilizer use rate ( F ) and crop type ( c ) are most significant in influencing the soil moisture at the three soil depths considered. Here we take the 20–50 cm soil layer, which comprises a large portion of root zone 28 29 and is directly affected by transpiration, to illustrate the correlated effects of declining soil moisture. The analysis yields slopes of 4.1 × 10 −4 (m 3 m −3 mm −1 yr), −3.0 × 10 −4 (m 3 m −3 kg −1 ha yr), −0.013 and −0.026, for P , F , crop group 2 (i.e., c 2, wheat) and group 3 (i.e., c 3, maize and rapeseed), respectively – see model (1) in Methods.…”
Section: Resultsmentioning
confidence: 99%
“…Summer maize has a fibrous root system that is divided into three categories: primary root, secondary root, and aerial root ). Previous studies indicated that the vast majority of summer maize roots grow in the upper 40 cm of soil (Yi et al, 2009;Liu et al, 2009). Root biomass reaches its maximum at tasseling, pin silk, or milk stages (Yi et al, 2009), and the rooting depth development can be described as a sine function with time (Borg and Grimes, 1986).…”
Section: Relationship Between Root Distribution and Water Uptakementioning
confidence: 99%
“…Furthermore, Haden et al [28] have reported that roots are the main contributor to SOC formation. Based on Hou et al [59] and Liu et al [60], the roots of wheat and maize are mainly concentrated in the 0-0.2 m soil layer, while for potato, roots are mainly located in the 0-0.1 m soil layer [61]. These differences in the rooting depth patterns among the studied crop types could affect the various vertical placements of SOC within the soil profile [62].…”
Section: Effects Of Different Rotation Patterns On Soc and Soil Phmentioning
confidence: 99%